Pelatihan Pembuatan Media Pembelajaran Berbasis Canva untuk Guru-Guru Sekolah Menengah Pertama di Kota Bekasi - Partasiwi, Nurashri; Safitri, Dini; Syaadah, Rika Siti (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Improving the quality of learning requires learning media that functions as a means of supporting successful learning so that it is able to compete in the era of globalization. One thing that can be used as a learning medium in junior high schools is Canva, which is an online design program that provides various learning media such as presentations, resumes, posters, pamphlets, brochures, graphics, infographics, banners, bookmarks, bulletins, and so on. The aim of this training activity is to increase the knowledge and abilities of junior high school teachers in Bekasi City in creating learning media using the Canva application. The methods used are theory, practice and discussion. After attending this training, teachers have more skills in using and creating learning media using the Canva application so they can convey mathematics material to students more easily and can help prepare reports, create teaching materials or other things faster and more creatively. So that students are more active in learning and can improve the quality of the learning process and learning outcomes of junior high school students, especially in Bekasi City.